An Efficient Chaotic Cryptosystem for Real-time MPEG Video Encryption Algorithm using Arnold’s Cat Map and Henon Map - Bhuvaneswari, K.; Mahesh, K. (IJRDO -Journal of Computer Science Engineering, 2017)
Rapid growth in network communication, there is need development inorder to provide the security for sensitive data from leakages. Many algorithms were designed for past years but they are not well proficient while concerning multimedia elements such as image and video due to high complexity of encoded /decoded, high correlation among all the pixels. Chaos based encryption algorithm has suggested to deal with these problems because it has desirable features of generate pseudo random number, sensitivity to initial conditions. A multimedia element video is bounded of audio and image so video encryption is to consider crucial part and critical task. The intent of proposed method is to secure the secret video clip by encryption using Arnold’s Cat Map and Henon chaotic map. In this method, video is extracted into frames and equal size of chaotic sequences is generated. Original pixel values are shuffled using cat map and its result is XORed with the chaotic sequences of Henon Map. Further, security of the implemented algorithm is evaluated by experiments on different input video clips and result produced in less complexity with high security. Finally conclude that this system is efficacy and provides two layers of security for transmission of multimedia element video.